Bilateral internal iliac artery ligation in trauma patients with severe pelvic hemorrhage: A systematic review - Soon Tak Jeong; Do Wan Kim; Wu Seong Kang (PLoS ONE, 2025)
Introduction Severe pelvic hemorrhage significantly contributes to mortality in trauma patients, yet the most effective treatment for severe pelvic injuries remains unclear. This systematic review evaluates the mortality and morbidity associated with bilateral internal iliac artery ligation (BIIAL) in patients experiencing severe hemorrhage from traumatic pelvic fractures. Methods Comprehensive searches were conducted in MEDLINE PubMed, EMBASE, and Cochrane databases until February 7, 2024, to identify relevant articles. The risk of bias in observational studies was assessed using the ROBINS-I tool, which evaluates bias risk in nonrandomized intervention studies. The primary outcome was mortality following BIIAL, with the secondary outcome being complications related to the procedure. Results The review included eight studies, all observational. The overall mortality rate after BIIAL ranged from 45.0% to 76.9%. Ischemic complications from BIIAL were infrequent. A high and unclear risk of bias due to confounding and participant selection was noted across the studies. Four studies highlighted distinct indications for BIIAL compared to angioembolization. BIIAL was employed for patients with severe hemodynamic instability or when angiography was not available. Conclusion Due to geographical limitations and significant heterogeneity among the studies reviewed, the true effect size of BIIAL remains indeterminate. Nevertheless, further prospective studies with robust designs are necessary. BIIAL holds potential as a viable option when angioembolization is not accessible or in cases of critical patient instability.